2021
DOI: 10.1002/pchj.425
|View full text |Cite
|
Sign up to set email alerts
|

Family accommodation in Chinese individuals with obsessive‐compulsive disorder

Abstract: Family accommodation is a common, treatment-relevant construct related to obsessive-compulsive disorder (OCD) severity and treatment outcome. This initial study examined the nature, incidence, and clinical correlates of family accommodation in Chinese adults with OCD and their relative or person in a close relationship. One hundred four outpatients diagnosed with OCD completed selfreport measures of obsessive-compulsive, anxiety, and depression symptoms. Additionally, the individuals with OCD and a relative co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…In other studies, family accommodation was found to be widespread among Chinese OCD patients and was significantly positively correlated with the severity, dysfunction, anxiety, and depression of OCD, which is basically consistent with the findings of our study. 54 Other studies have shown that the more serious the family accommodation, the higher the severity of OCD symptoms and the greater the risk of withdrawal from treatment 28 and that family accommodation can be used as a predictor of the outcome of OCD treatment. 55 In addition, researchers have demonstrated the importance of assessing symptom severity in conjunction with family accommodation when evaluating OCD patient functional impairment.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, family accommodation was found to be widespread among Chinese OCD patients and was significantly positively correlated with the severity, dysfunction, anxiety, and depression of OCD, which is basically consistent with the findings of our study. 54 Other studies have shown that the more serious the family accommodation, the higher the severity of OCD symptoms and the greater the risk of withdrawal from treatment 28 and that family accommodation can be used as a predictor of the outcome of OCD treatment. 55 In addition, researchers have demonstrated the importance of assessing symptom severity in conjunction with family accommodation when evaluating OCD patient functional impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural values and norms affect caregiving experiences, the cultural determinants of caregiving responsibilities or the caregiving hierarchy, and the values and norms underlying the decision to provide care [ 29 ]. High FA was reported in studies using FAS-PV in Chinese society, and this result was interpreted to be related to family-centered and collectivist cultural structure [ 30 ].The most frequently observed FA behaviors in the present research were the provision of reassurance for obsessions and compulsions. Similar to the results of our study, in previous studies using the same measurement method, waiting for the affected person to complete compulsive behaviors and providing reassurance regarding OCD-related concerns were the most frequently reported specific behaviors [ 17 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, significant positive correlation was observed in this study between FA and severity of OCD (total DOCS score), depression, anxiety, and psychological inflexibility. Inconsistent results concerning the relationship between depression and anxiety and FA have been reported in the literature [ 17 , 27 , 30 , 34 ]. In addition, severity of disease emerged as a significant predictor of FA at regression analysis.…”
Section: Discussionmentioning
confidence: 99%